2009
DOI: 10.1094/pdis-93-9-0965b
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Freesia sneak virus in Freesia sp. in Virginia

Abstract: In the spring of 2008, freesia, cvs. Honeymoon and Santana, with striking virus-like symptoms similar to freesia leaf necrosis disease were received by the Virginia Tech Plant Disease Clinic from a cut-flower nursery in Gloucester, VA and forwarded for analysis to the USDA-ARS Floral and Nursery Plants Research Unit in Beltsville, MD. Approximately 25% of the plants had coalescing, interveinal, chlorotic, whitish, necrotic or dark brown-to-purple necrotic spots on leaves. Symptomatic plants were scattered with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Lettuce big-vein associated virus (LBVaV) (genus Varicosavirus) and Mirafiori lettuce bigvein virus (MiLBVV) (genus Ophiovirus) are transmitted by Olpidium virulentus, a noncrucifer strain of O. brassicae [60], and Lettuce ring necrosis virus (LRNV) (genus Ophiovirus) is also transmitted by O. brassicae [64]. A new soil-transmitted ophiovirus associated with freesia leaf necrosis disease [68], Freesia sneak virus (FreSV) is likely involved [69,72]. In lettuce big-vein disease it has been shown that zoospores of Olpidium released from sporangia contain the virus in their protoplast and transmit to the roots.…”
Section: Virus Transmissionmentioning
confidence: 99%
“…Lettuce big-vein associated virus (LBVaV) (genus Varicosavirus) and Mirafiori lettuce bigvein virus (MiLBVV) (genus Ophiovirus) are transmitted by Olpidium virulentus, a noncrucifer strain of O. brassicae [60], and Lettuce ring necrosis virus (LRNV) (genus Ophiovirus) is also transmitted by O. brassicae [64]. A new soil-transmitted ophiovirus associated with freesia leaf necrosis disease [68], Freesia sneak virus (FreSV) is likely involved [69,72]. In lettuce big-vein disease it has been shown that zoospores of Olpidium released from sporangia contain the virus in their protoplast and transmit to the roots.…”
Section: Virus Transmissionmentioning
confidence: 99%
“…The symptoms described in ranunculus plants were mosaic, mottle and distortion of leaves and stems, giving the name Ranunculus white mottle virus. For years the virus was consistently isolated from plants and found in mixed infection with potyvirus (Vaira et al, 1997(Vaira et al, , 2009. They could mechanically transmit the virus to several herbaceous hosts (N. benthamiana and N. clevelandii), and by EM, in negative stain the particle morphology appeared similar to CPsV, Tenuivirus and Bunyaviridae (Vaira et al, 1996(Vaira et al, , 1997.…”
Section: In Ornamental Plants: Tulip Mild Mottle Mosaic Virus Ranuncmentioning
confidence: 99%
“…Thus began the study of the ophioviruses Ranunculus white mottle virus (RWMV) (Vaira et al, 1997), Mirafiori lettuce big-vein virus (MiLBVV) (Roggero et al, 2000), Lettuce ring necrosis virus (LRNV) (Torok et al, 2002(Torok et al, , 2003 and Freesia sneak virus (FreSV) (Vaira et al, 2006). Most, if not all these viruses have been found around the world (Roistacher 1993;Navarro et al, 2004;Martin et al, 2006;Ghazal et al, 2008;Vaira et al, 2007Vaira et al, , 2009Plesko et al, 2009;Barcala Tabarrozzi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Ophioviridae is a family of negative strand RNA plant viruses whose type specie is Citrus psorosis virus (CPsV). Ophioviruses cause major diseases in crops of citrus, lettuce, blueberry and ornamental plants (Moreno et al, 2015;Morikawa et al, 1995;Roggero et al, 2000;Thekke-Veetil et al, 2014;Torok and Vetten, 2010;Vaira et al, 2009;Vaira et al, 1997). Their genome is divided into 3 segments for CPsV and 4 segments for Mirafiori lettuce bigvein virus (MiLBVV) (Vaira et al, 2011).…”
Section: Introductionmentioning
confidence: 99%